Gambaran Stigma Pada Mantan Narapidana Teroris - Prayitno, Salma Salsabila; Nur Alfian, Ilham (Jurnal Syntax Fusion, 2023)
This study aims to describe the stigma against former terrorist convicts. The research method uses descriptive qualitative. Data collection was held out by interviewing four theoretical ex-convicts and the data analysis used was thematically analysis techniques. From the results of the analysis, it's known that former terrorist inmates receive stigma from their extended family, society, employers, and the surrounding community. The description of stigma is discussed through the components of stigma, stigma mechanisms, and coping with former terrorist prisoners facing stigma. Accepted stigma consists of components of labeling, stereotypes, separation, and discrimination as well as loss of status. Stigma causes former terrorist prisoners to experience negative behavior and discrimination, automatic stereotype activation behavior, and identity threats. In dealing with stigma, former terrorist convicts develop coping strategies by solving planned problems and seeking social groups on coping strategies that focus on problems, as well as aspects of self-control and keeping distance on coping strategies that focus on emotions.